Eriobotrya Belongs to Rhaphiolepis (Maleae, Rosaceae): Evidence From Chloroplast Genome and Nuclear Ribosomal DNA Data - Liu, Bin-Bin; Liu, Guang-Ning; Hong, De-Yuan; Wen, Jun (Frontiers in Plant Science, 2020)
The Eriobotrya-Rhaphiolepis (ER) clade consists of about 46 species distributed in East and Southeast Asia. Although Eriobotrya and Rhaphiolepis have been supported to form a clade, the monophyly of Eriobotrya and Rhaphiolepis at the genus level has never been well tested and their phylogenetic positions in Maleae still remain uncertain. This study aims to reconstruct a robust phylogeny of the ER clade in the framework of Maleae with a broad taxon sampling and clarify the phylogenetic relationship between Eriobotrya and Rhaphiolepis. This study employed sequences of the whole plastome (WP) and entire nuclear ribosomal DNA (nrDNA) repeats assembled from the genome skimming approach and included 83 samples representing 76 species in 32 genera of Rosaceae, especially Maleae. The Maximum Likelihood (ML) and Bayesian Analysis (BI) based on three datasets, i.e., WP, coding sequences of plastome (CDS), and nrDNA, strongly supported the paraphyly of Eriobotrya, in which Rhaphiolepis was nested within. Our plastid tree clarified the sister relationship between the ER clade and Heteromeles, and the nrDNA tree, however, did not resolve the phylogenetic placement of the ER clade in Maleae. Strong incongruence between the plastid and the nuclear trees is most likely explained by hybridization events, which may have played an important role in the evolutionary history of the ER clade. The molecular, morphological, and geographic evidence all supports the merge of Eriobotrya with Rhaphiolepis, which has the nomenclatural priority. We herein transferred 35 taxa of Eriobotrya to Rhaphiolepis. We also proposed a new name, Rhaphiolepis loquata B.B.Liu & J.Wen, for the economically important loquat, as the specific epithet “japonica” was pre-occupied in Rhaphiolepis.